Efeitos do turno de rega e cobertura morta na cultura do alho na serra da Ibiapaba, Ceará. II. Produção e qualidade dos bulbos Irrigation frequency and mulching effects on gerlic culture in Ibiapaba region, State of Ceará, Brazil. II. Bulb yeld and qualit (Revista Ciência Agronômica, 2023)
RCA